An Experimental Study of DC and AC Load Effects on Photovoltaic Systems - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2008)
Clean and renewable energy production is getting more attractive due to global warming, environmental factors and decrease in conventional energy sources. Photovoltaic cells will be a good alternative against the conventional energy sources in the near future, with their decreasing costs and increasing efficiencies. Photovoltaic cells (PV) are exposed to a lot of various loads depending on their increasing usage areas. In this study different load effects on PV cells are examined experimentally. D.C. and A.C. load behaviors are analyzed in switching and in steady state regime and their power-time curves are obtained for the demand of system power. Negative effects of the inverter circuit, which is used for feeding A.C. loads on the system, are expressed experimentally.
Keywords: Photovoltaic Cell; Power LED; Compact Fluorescent Lamp; Induction Motor